2012
DOI: 10.1097/mog.0b013e3283505852
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical cobalamin deficiency

Abstract: The story of SCCD, which is severalfold times more common in the elderly than clinical cobalamin deficiency but also differs from it in arising only infrequently from severe malabsorption and thus being less likely to progress, continues to evolve. Preventive benefits need to be confirmed and expanded, and will require fuller understanding of SCCD pathophysiology, natural history, and health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 70 publications
0
41
0
2
Order By: Relevance
“…However, the optimal testing for diagnosis of SCCD continues to be investigated. 3 As recently reported, all biomarkers can produce falsely abnormal results, and none is a diagnostic gold standard. 3,5 Secondly, Dr Grzybowski points out that the reason for vitamin B12 deficiency in our patients was not given and intrinsic factor (IF)-related malabsorption was not verified.…”
Section: 1mentioning
confidence: 99%
See 4 more Smart Citations
“…However, the optimal testing for diagnosis of SCCD continues to be investigated. 3 As recently reported, all biomarkers can produce falsely abnormal results, and none is a diagnostic gold standard. 3,5 Secondly, Dr Grzybowski points out that the reason for vitamin B12 deficiency in our patients was not given and intrinsic factor (IF)-related malabsorption was not verified.…”
Section: 1mentioning
confidence: 99%
“…3 As recently reported, all biomarkers can produce falsely abnormal results, and none is a diagnostic gold standard. 3,5 Secondly, Dr Grzybowski points out that the reason for vitamin B12 deficiency in our patients was not given and intrinsic factor (IF)-related malabsorption was not verified. The cause of vitamin B12 deficiency and IF was not evaluated in our work because it has been shown that the causes of SCCD are unknown in more than 60% of cases.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations